Iron Chelation in Local Infection - Cassidy Scott; Gaurav Arora; Kayle Dickson; Christian Lehmann (Molecules, 2021)
Iron is an essential element in multiple biochemical pathways in humans and pathogens. As part of the innate immune response in local infection, iron availability is restricted locally in order to reduce overproduction of reactive oxygen species by the host and to attenuate bacterial growth. This physiological regulation represents the rationale for the therapeutic use of iron chelators to support induced iron deprivation and to treat infections. In this review paper we discuss the importance of iron regulation through examples of local infection and the potential of iron chelation in treating infection.